Duodenal tuberculosis mimicking superior mesenteric artery syndrome - Gawade, Harshad; Singh, Gurjit; Ali, Iqbal; Patil, Abhijit; Chandan, Amit (International Surgery Journal, 2016)
Tuberculosis of stomach and duodenum is quite uncommon. Its preoperative diagnosis still remains a challenging problem for surgeons. Herein, we report the case of isolated abdominal tuberculosis in a 28 years old male presenting with features of gastric outlet obstruction due to stricture in duodenum. Oesophagogastroscopy revealed doubtful extrinsic compression of first part of duodenum with mild gastritis. CECT abdomen showed pronounced dilatation of stomach, 1st and 2nd part of duodenum with narrowing and compression of 3rd part of duodenum between superior mesentric artery and aorta; suggesting superior mesenteric artery syndrome (SMA). He was taken up for exploration which revealed peritoneal, small and large bowel mesentery and mesocolon seedlings. Mesenteric lymphadenopathy was seen and duodenum showed narrowing between 1st and 2nd part of duodenum with proximal dilated and distal narrow duodenum without any compression by SMA. Duodeno-duodenostomy was done. Histopathological examination of biopsied mesenteric lymph node was consistent with the features of tuberculosis. Patient was started on anti-tubercular therapy. His symptoms were relieved and he gained weight rapidly.